QT interval is a heritable quantitative trait with evidence of linkage to chromosome 3 in a genome-wide linkage analysis: The Framingham Heart Study - Newton-Cheh, Christopher; Larson, Martin G; Corey, Diane C; Benjamin, Emelia J; Herbert, Alan G; Levy, Daniel; D'Agostino, Ralph B; O'Donnell, Christopher J (Heart rhythm, 2005)
To identify genomic regions linked to QT interval duration in an unselected population. QT interval prolongation is associated with increased risk of sudden cardiac death and coronary heart disease and may result from acquired conditions or inherited ion channel defects. The influence of genetic variants on QT interval length in apparently healthy individuals is uncertain. We studied subjects from the Framingham Heart Study in whom 12-lead ECGs were available from regular clinic examinations. QT, QT-peak, and RR intervals were measured using digital calipers. A 10-centiMorgan (cM) density genome-wide scan was performed in a subset of the largest families having at least two members with ECG phenotypes (326 families). Variance components methods (Genehunter) were used. Evidence was observed for significant heritability of the QT interval (h(2) 0.35; 95% CI, 0.29-0.41), QT-peak interval (h(2) 0.37; 95% CI, 0.29-0.45), and calculated JT interval (h(2) 0.25; 95% CI, 0.19-0.31). In the genome-wide linkage analysis, we found suggestive evidence for linkage of the QT interval 19 to 48 cM from the tip of the short arm of chromosome 3 (maximum two-point LOD score 3.00, maximum multipoint LOD score 2.71). After fine-mapping with seven microsatellite markers, the peak multipoint LOD score rose to 2.84 at 24.4 cM. The region of linkage contains potassium and sodium channel genes, including the SCN5A gene, which has been implicated in one form of the long QT syndrome and in the Brugada syndrome. QT and related ECG intervals are heritable traits in a large unselected population. We provide suggestive evidence for a quantitative trait locus on chromosome 3 influencing QT interval duration. Further studies are warranted to identify genes that influence QT interval variation and to determine the role of heritable factors in life-threatening QT prolongation.